GAMBARAN PENGETAHUAN TENTANG COVID-19 PADA MASYARAKAT DI DESA BARU DUSUN 1 KECAMATAN PANCUR BATU TAHUN 2021 - Helinida Saragih; Agustaria Ginting; Gunawan Pelan Pincer Manalu (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Coronavirus is a virus that can cause mild symptoms as well as severe symptoms, which have never been previously found in humans. Coronavirus can cause respiratory problems characterized by flu symptoms, fever, shortness of breath, cough with phlegm, to cause heavy breathing such as lung infection with an incubation period of 5-6 days with the longest incubation of 14 days results showed that out of 95 respondents, 55 respondents (57.9%) had good knowledge and 40 respondents (42.1%) had sufficient knowledge. The results of the research show that the people in Desa Baru Dusun 1 Pancur Batu District have good knowledge. It is hoped that the public will continue to follow health protocols such as wearing masks, washing hands frequently, social distancing or maintaining distance to prevent the spread of COVID-19.Knowledge of Covid-19 is information that must be possessed in an effort to reduce the spread or transmission of Covid-19. The reason the researchers conducted this research, was due to the lack of public knowledge about Covid-19 which caused them not to wear masks and comply with health protocols in carrying out their daily activities. Based on the preliminary survey, it was found that out of the 12 people selected, 5 people (41.6%) did not know about COVID-19. This study aims to determine the description of public knowledge about COVID-19 in Desa Baru Dusun 1 Pancur Batu District. The research method used is to use a descriptive research design. The population in this research was 1816 people. The sampling technique in this study was purposive sampling with a total sample of 95 people. The results showed that out of 95 respondents, 55 respondents (57.9%) had good knowledge and 40 respondents (42.1%) had sufficient knowledge. The results of the research show that the people in Desa Baru Dusun 1 Pancur Batu District have good knowledge. It is hoped that the public will continue to follow health protocols such as wearing masks, syringes, maintaining social distancing or maintaining distance to prevent COVID-19.